The Plain Janes - Castellucci, Cecil, 1969- (Minx, 2007)
After a bombing in the city, Jane's parents move to a suburb where she befriends three outcasts--all named Jane--and starts a group called People Loving Art in Neighborhoods, which tries to enrich their community with art but instead is viewed as a threat.